Customising excitation properties of polycyclic aromatic hydrocarbons by rational positional heteroatom doping: the peri-xanthenoxanthene (PXX) case. Issue 21 (12th May 2022) - Valentini, Cataldo; Gowland, Duncan; Bezzu, C. Grazia; Romito, Deborah; Demitri, Nicola; Bonini, Nicola; Bonifazi, Davide
Abstract : In this paper we tackle the challenge of gaining control of the photophysical properties of PAHs through a site-specific N-doping within the structural aromatic framework. Abstract : In this paper we tackle the challenge of gaining control of the photophysical properties of PAHs through a site-specific N-doping within the structural aromatic framework. By developing a simple predictive tool that identifies C(sp 2 )-positions that if substituted with a heteroatom would tailor the changes in the absorption and emission spectral envelopes, we predict optimal substitutional patterns for the model peri -xanthenoxanthene (PXX ) PAH. Specifically, TDDFT calculations of the electron density difference between the S1 excited state and S0 ground state of PXX allowed us to identify the subtleties in the role of sites i.e., electron donating or withdrawing character on excitation. The replacement of two C(sp 2 )-atoms with two N-atoms, in either electron donating or withdrawing positions, shifts the electronic transitions either to low or high energy, respectively. This consequently shifts the PXX absorption spectral envelop bathochromically or hypsochromically, as demonstrated by steady-state absorption spectroscopic measurements. Within the series of synthesised N-doped PXX, we tune the optical band gap within an interval of ∼0.4 eV, in full agreement with the theoretical predictions. Relatedly, measurements show the more blueshifted the absorption/emission energies, the greater the fluorescence quantum yield value (from ∼45% to ∼75%). On the other hand, electrochemical investigations suggested that the N-pattern has a limited influence on the redox properties. Lastly, depending on the N-pattern, different supramolecular organisations could be obtained at the solid-state, with the 1, 7-pattern PXX molecule forming multi-layered, graphene-like, supramolecular sheets through a combination of weak H-bonding and π–π stacking interactions. Supramolecular striped patterned sheets could also be formed with the 3, 9- and 4, 10-congeners when co-crystallized with a halogen-bond donor molecule.